India`s energy security the changing dynamics - Singh, Bhupendra Kumar (New Delhi Pentagon Energy Press, 2010)
Evaluation of the India's energy policy with reference to importance of Persian Gulf in spite of diversification.
Includes bibliographical references (p. [232]-255) and index.
Keywords: Energy policy -- India; Oil industries -- Government policy -- India; India -- Commerce -- Persian Gulf; Persian Gulf -- Commerce -- India